Wound fluid sampling methods and analysis of cytokine mRNA expression in ulcers from patients with diabetes mellitus - Beatriz Barbieri; Amanda Silva; Joseane Morari; Flavia C. Zanchetta; Bianca Oliveira; Alexis Trott; Eliana P. Araújo; Geraldo Paula; Beatriz Guitton Renaud Baptista de Oliveira; Bruna Maiara Ferreira Barreto Pires; Maria Helena Melo Lima (Regenerative Therapy)
The development of diabetic foot ulcers is a common and severe complication of diabetes that can significantly affect quality of life. The physiological healing cascade does not progress tissue repair in diabetic foot ulcerations in a timely manner. Serum markers from foot ulcers have been used to characterize the healing process of the diabetic foot using various collection techniques. This study aimed to compare the use of cervical brushes and the Levine technique to collect wound fluid from foot ulcers of people with diabetes in order to determine the presence of cytokines. The collected material was used for gene expression analysis of macrophage/monocyte-associated cytokines IL1-β, IL-6, TNF-α, regulatory cytokine IL-10 and growth factor TGFβ, via quantitative polymerase chain reaction (qPCR). Both collection methods produced sufficient amounts of RNA, but significantly more RNA was collected using a cervical brush (brush 224.82 ng/μL vs. Levine 80.90 ng/μL p = 0.0001). Significantly higher levels of expression of the following cytokine genes were detected in samples collected using a cervical brush: IL1-β (p = 0.0001), IL-6 (p = 0.0106), IL-10 (p = 0.0277) and TGFβ (p = 0.0002). Understanding why some wounds are difficult to heal is important for developing more effective treatments, and biomarkers may be useful for predicting the healing trajectory. These results demonstrate that it is possible to collect material from the wound bed for RT-qPCR analysis, and the cervical brush proved to be a simple and rapid method for monitoring cytokine gene expression.